Handbook of research on business and technology incubation and acceleration : a global perspective - Mian, Sarfaz A.; Klofsten, Magnus; Lamine, Wadid (Research handbooks in business and management series, 2021)
"This pioneering work explores both the theory and practice of business and technology incubation and acceleration over the past six decades as an approach to new venture creation and development. With a global scope, the Handbook examines incubation concepts, models, and mechanisms, providing a research-based analytical foundation from which to understand the emerging role of modern incubators, accelerators, science parks, and related support tools in building modern entrepreneurship ecosystems for promoting targeted economic development. Featuring contributions from internationally renowned scholars and practitioners, the Handbook covers four major themes: understanding incubation and acceleration; incubation mechanisms and entrepreneurship ecosystem development; national and regional incubation policy studies; and incubation practice and assessment. Chapters investigate the expanding importance of newer models and novel modes of new venture support such as smart launching through focused training, mentoring, and financing. This Handbook will help to equip policy makers, facility and program managers, investors, and entrepreneurs with the knowledge to handle support for future business and technology ventures more confidently and effectively. It also provides a deeper understanding of the incubation approach for researchers and scholars of entrepreneurship, innovation, and economic development"--